Car Plate Number Reader (CPNR) using image processing for Polis Bantuan UiTM Jasin / Mohammad Syamil Abd Maulop - Abd Maulop, Mohammad Syamil (2017)
Polis Bantuan (PB) department is a unit in UiTM Jasin that was formerly known as the Security Unit that serves to create and maintain the ideal atmosphere, peace and security on campus. The mission of this unit is to provide professional service, integrity and accountability. Polis Bantuan (PB) UiTM Jasin given full responsibility for security management around campus. This project is focused on the process to generate fine ticket, which is involved of process to get the vehicle plate number by using image processing technique which is Optical Recognition Character (OCR) and the details of the vehicle including the vehicle’s owner details. This system will help the user to search the details through the image of the vehicle plate number that captured by the user. This can help to reduce the process that need to be done and time taken to check for the details. This project is carried out with an aim to implement the Car Plate Number Reader (CPNR) using the three-tier architecture and Mobile Application Development Life Cycle (MADLC) is carried out as methodology to develop the system. However, this project only covers three phases and the phases that involved are Identification, Design and Develop. As a result, a prototype of Car Plate Number Reader (CPNR) is produced together with documentations of Software Requirements Specification (SRS) and Software Design Document (SDD). Thus, for future works this mobile application can be used by all students and staff at all UiTM in Malaysia and hope it can be used by all platforms of mobile application in the world. Besides that, this mobile application can be enhanced in future by adding more features and enhanced the user interface. This will increase the performance and productivity of the mobile application that user can maximize it the usability.